Range-wide conservation genetics of Buff-breasted Sandpipers (Tryngites subruficollis) - Lounsberry, Zachary T.; Almeida, Juliana B.; Grace, Tony; Lanctot, Richard B.; Liebezeit, Joe; Sandercock, Brett K.; Strum, Khara M.; Zack, Steve; Wisely, Samantha M. (My University, 2013)
Range-wide monitoring of shorebirds (Aves: Charadriiformes) suggests that many species are declining. For most species, it is unknown whether distinct population units exist, which makes management and conservation difficult. One shorebird of conservation concern, the Buff-breasted Sandpiper (Tryngites subruficollis), is a New World migrant that breeds at Arctic latitudes in North America and Russia and winters in southeastern South America. We conducted a molecular survey of samples representing each of three migratory regions (breeding, migration, and wintering) using nine polymorphic microsatellite loci and 1.5 kb of highly variable mitochondrial DNA (mtDNA) from the cytochrome b gene and mtDNA control region. We analyzed contemporary population structure, demographic trends, and phylogeographic patterns. Overall, microsatellite and mtDNA analyses revealed that Buff-breasted Sandpipers are panmictic both regionally and at a global scale, with no signal of a recent genetic bottleneck. The mtDNA analyses revealed a pattern of haplotype diversity consistent with an expansion from a single refugium (Tajima's D: -2.27, P < 0.01; Fu's F[subscript s]: -30.6, P < 0.0001), after the height of the Wisconsinan glaciation (8,400–45,000 years before present). Overall, our molecular analyses suggest that Buff-breasted Sandpipers should be treated as a single conservation unit, and management efforts for this species should focus on limiting future declines to ensure that genetic viability is maintained.
Keywords: Buff-breasted Sandpiper; Microsatellites; mtDNA; Phylogeography; Population bottleneck; Shorebird; Tryngites subruficollis; Wader